Development of the person-child: Awareness of oneself and of others through motor activity - Valentini, Manuela; Montesi, Michela; Federici, Ario (American Journal of Social Sciences and Humanities, 2024)
This article, structured through in-depth and rigorous bibliographical research, focuses on the importance of movement and the body in nursery school as privileged elements for interacting with the world by starting one's own path of acquiring a personality style. In fact, the school, together with the family and the social sector, has the great responsibility of instructing and educating with all the knowledge for a complete education, taking care of and welcoming subjects of developmental age. One of its main purposes is to initiate the full development of the personality for complete maturation by providing knowledge that uses all languages (verbal and non-verbal) with concrete and tangible skills for the future man citizen. We focus on how, from early childhood, the body connects the self with things, with the environment, and with others, enhancing everyone's experience from an early age, from cognitive, sensorial, emotional points of view, social, and relational through the body, placing it as the protagonist and creating contexts in which to build meanings and diversified paths. The emphasis is on carrying out multiple and different recreational-motor activities in a positive and stimulating environment, leaving the child time to experiment and internalize at his own pace, allowing him to build his self-image (perception, knowledge, conscience), gradually exploring and learning through it.